Is There an Association of Vascular Disease and Atherosclerosis in Children and Adolescents With Obesity and Non-alcoholic Fatty Liver Disease? - Karjoo, Sara (Frontiers in Pediatrics, 2018)
Carotid intima media thickness (cIMT) and brachial flow-mediated dilation (FMD) evaluated by ultrasound are non-invasive markers of atherosclerosis. Increased cIMT in adults has been correlated to early vascular damage. Several studies show similar correlations of elevated cIMT in children with obesity, hyperlipidemia, and metabolic syndrome. Additionally, several articles have correlated non-alcoholic fatty liver disease (NAFLD) with elevated cIMT, indicating early atherosclerosis. It is alarming that these vascular changes may be seen in children as young as 10 years of age. Children with NAFLD may also have an increased pulse wave velocity that correlates to increased arterial stiffness and increased left ventricular dimension, mass, and diastolic dysfunction. These articles are persuasive, indicating a correlation of Pediatric NAFLD and early vascular disease. However, study limitations include the use of elevated alanine aminotransferase (ALT) and echogenic changes on ultrasound that may have low accuracy to identify NAFLD. Ultrasound has low sensitivities and specificities for detection of NAFLD and therefore is not recommended for diagnosis. In comparison, studies that used liver biopsy or proton magnetic resonance spectroscopy to identify NAFLD did not find a correlation with elevated cIMT or reduction in FMD. Due to these conflicting findings, more studies looking at cIMT and FMD changes in children with NAFLD are needed with more accurate diagnostic methods for steatosis to identify if there truly is a correlation of increased liver steatosis to early atherosclerosis.